A qualitative inquiry into Islamic home financing: evidence from Malaysia - Loke, Kevin K. W.; Mohd Thas Thaker, Hassanudin * (Emerald, 2017)
Purpose: The purpose of this paper is to explore the development of Islamic home financing and some of its practical issues. In addition, the study also intends to draw attention to some recommendations to the issues highlighted from the viewpoint of industrial experts. Design/methodology/approach: The methodology for this study follows the qualitative research approach which aims to capture the thoughts and extensive knowledge of a few related experts in the field. Eight respondents who are mainly scholars and bankers in Islamic banking were selected for the interview purpose. A semi-structured interview was adopted to investigate a series of themes concerning the Islamic home financing in Malaysia. Findings: In terms of development, the findings showed that a majority of the participants agreed that the Islamic banking and finance (IBF) is developing in line with its counterpart – the conventional banks. This is due to its innovation in products as well as offering a variety of financial products including home financing. Some of the practical issues highlighted by the respondents include pricing, adherence to conventional framework and interest rate movement. Islamic home financing is argued to be much more expensive and faces difficulty in working within a conventional framework. The issue of interest rate movement is also becoming a major hurdle in Islamic banking due to the absence of a proper benchmark for IBF. At present, IBF still follows the benchmark set by its conventional counterpart. Furthermore, the respondents also believed that the product of home financing, together with other financial products, are not in line with the teaching of Shariah principles and guideline. In addressing those issues, the respondents provided some suggestions to counter those problems, which include promoting Islamic home financing, particularly in terms of Musharakah Mutanaqisah (MM), ensuring the transparency of products, strengthening due diligence, legal aspect and others. Research limitations/implications: This study is limited in terms of the relatively small number of respondents used to generate its findings. Time constraint is another limiting factor of the research. Additionally, potential respondents in a higher position were unable to take part in the study. Due to these factors, the generalisation of the study’s findings will be visibly restricted. Practical implications: This paper is expected to generate several practical implications. Firstly, the study’s exploration of the issues surrounding home financing will likely provide a general overview of the recent development in Islamic banking and the challenges it faces. Consequently, this will indirectly help policymakers and bankers alike to design a better policy when dealing with Islamic home financing issues. In the review of various literatures in the field, a majority of research studies were observed to mainly focus on a quantitative approach. Hence, in terms of methodological innovation, the study’s use of qualitative inquiry based on an interview method may provide a deeper understanding of the matter. The resolutions proposed by the various experts are hoped to contribute to shaping a better framework and system in Islamic and conventional home financing in Malaysia. Originality/value: Despite having many literatures revealing mixed results concerning Islamic home financing, especially the Bai Bithaman Ajil and MM, addressing the issues of Islamic home financing, particularly from an expert perspective, has been lacking. The majority of research studies claim those issues from a theoretical viewpoint rather than a practical one. With this gap and lack of initiative, the current study is motivated to undertake an in-depth analysis on the issues of Islamic home financing and how to address those arising issues from an industrial expert’s point of view via a qualitative approach.